Implementation of the Game-Based Learning (GBL) Learning Model Assisted by the Educandy Application to Improve Learning Motivation and Student Economic Learning Outcomes - Intan Sepri Lioni; Friyatmi Friyatmi (Universitas Negeri Padang, 2024)
Using the Game-Based Learning (GBL) approach with the help of the Educandy application, this study seeks to increase student motivation and learning outcomes. Low motivation and student learning results from the saturation and inefficiency of traditional teaching methods are the primary issues. The Pretest-Posttest Control Group design was used in a pseudo-experimental study carried out at SMA Negeri 1 Sungai Limau. Purposive sampling was used to choose the sample, while learning outcome assessments and motivation questionnaires were used as tools. Compared to traditional learning, the independent sample t-test findings demonstrated that using GBL with Educandy’s assistance significantly improved student motivation and learning outcomes. In summary, GBL combined with Educandy improves learning results and student motivation.